2020
DOI: 10.3390/molecules25225397
|View full text |Cite
|
Sign up to set email alerts
|

Lanostane Triterpenoid Metabolites from a Penares sp. Marine Sponge Protect Neuro-2a Cells against Paraquat Neurotoxicity

Abstract: The results of an investigation of the protective effects of five lanostane triterpenoids: 3β-acetoxy-7β,8β-epoxy-5α-lanost-24-en-30,9α-olide (1), 3β-hydroxy-7β,8β-epoxy-5α-lanost-24-en- 30,9α-olide (2), 29-nor-penasterone (3), penasterone (4), and acetylpenasterol (5), from a marine sponge, Penares sp., against paraquat-induced neuroblastoma Neuro-2a cell damage, are described. The influence of all compounds on viability of the Neuro-2a cells treated with paraquat (PQ) was studied with MTT and fluorescein dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Initially, cells were incubated in cultural flasks until sub-confluent (~80%). For testing, Neuro-2a cells were seeded in 96-well plates and experiments were started after 24 h [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Initially, cells were incubated in cultural flasks until sub-confluent (~80%). For testing, Neuro-2a cells were seeded in 96-well plates and experiments were started after 24 h [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The data were processed by MARS Data Analysis v. 3.01R2 (BMG Labtech, Ortenberg, Germany). The results were presented as a percentage of positive control data [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since some of the sponge-derived metabolites were included in clinical and preclinical trials showing their efficacy as modulators of immune response (Gunasekera et al 1989;Alcaraz and Paya 2006;Fattorusso and Taglialatela-Scafati 2009;Sagar et al 2010;Bibi et al 2017;Negi et al 2017;Karpinski 2019;Yurchenko et al 2020), the observation that characellide A is a potent in vitro activator of PBMC raising interesting perspectives on its potential pharmacological application.…”
Section: Discussionmentioning
confidence: 99%
“…of much research which has identified thousands of different natural products including 300 novel compounds with interesting pharmacological features (Faulkner 2000(Faulkner , 2001(Faulkner , 2002Sipkema et al 2005;Blunt et al 2006;Mehbub et al 2014). Interestingly, some of the sponge-derived metabolites have been included in clinical and preclinical trials showing their efficacy as anti-inflammatory (Alcaraz and Paya 2006), antitumoral (Negi et al 2017), immunosuppressive (Gunasekera et al 1989), neurosuppressive (Yurchenko et al 2020), antiviral (Sagar et al 2010), antimalarial (Fattorusso and Taglialatela-Scafati 2009), antibiotic (Bibi et al 2017) or antifungal (Karpinski 2019) compounds. Glycolipids represent the main components of several marine organisms and have been identified as potent activators of immune cells by binding to CD1d molecule (Wu et al 2008).…”
mentioning
confidence: 99%